2016
DOI: 10.1186/s12904-016-0145-0
|View full text |Cite
|
Sign up to set email alerts
|

Comfort experience in palliative care: a phenomenological study

Abstract: BackgroundPalliative care aims to provide maximum comfort to the patient. However it is unknown what factors facilitate or hinder the experience of comfort, from the perspective of inpatients of palliative care units. This lack of knowledge hinders the development of comfort interventions adjusted to these patients. The aim of this research is to describe the comfort and discomfort experienced by inpatients at palliative care units.MethodsA phenomenological descriptive study was undertaken. Ten inpatients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
13

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 44 publications
(43 reference statements)
1
24
0
13
Order By: Relevance
“…Compared with the findings of the study by Boyd et al (46), it is evident that the nurses who work in palliative care or have some experience with it, are interested in this area of practice and in furthering their knowledge of palliative care. They are willing to obtain new experiences in delivering palliative care to persons (31,44,46). This is in line with our study, where 95.7% (n = 421) of the nurses want to gain additional knowledge of palliative care with which they can provide adequate working skills of palliative care to the patient.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Compared with the findings of the study by Boyd et al (46), it is evident that the nurses who work in palliative care or have some experience with it, are interested in this area of practice and in furthering their knowledge of palliative care. They are willing to obtain new experiences in delivering palliative care to persons (31,44,46). This is in line with our study, where 95.7% (n = 421) of the nurses want to gain additional knowledge of palliative care with which they can provide adequate working skills of palliative care to the patient.…”
Section: Discussionsupporting
confidence: 82%
“…Specialised knowledge is very important, because many times, according to Kim and Hwang and Coelho et al. nurses have difficulties with regard to symptom management that may threaten the quality of care of persons with life‐threatening disease and accompanying disturbing symptoms. Furthermore, experts have concluded that there is still a lack of attention on how to deliver high‐quality knowledge in palliative care in undergraduate and postgraduate academic nursing programs .…”
Section: Discussionmentioning
confidence: 99%
“…The results highlight the experience of in-patients and add consistency to the evidence reported in other contexts and countries. [6,27,29,30] Thus, results give a comprehensive overview of comfort attributes throughout the perspective of palliative care patients, and open new perspectives to the operationalization of the comfort intervention.…”
Section: Discussionmentioning
confidence: 99%
“…However, and as reported in previous studies, comfort experience is frequently explored and understood through discomfort experiences or in the absence of comfort. [25][26][27] In this study, participants' experiences and views about comfort were represented in five main topics, regarding the physical, psychological, spiritual, social and environmental contexts. Findings highlight that participants experienced not only physical symptoms ("Me and what I feel") -such as pain, difficulty in resting, anorexia, asthenia and constipation -but also psychological ("Me and how I react") and spiritual problems ("Me and the meaning of my life"), such as lack of security, fear, sense of vulnerability, uncertainty, guilt and hopelessness.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the literature on GI, including scripts suggested by renowned authors in this area (Apóstolo, 2007), and the literature about comfort, including Katherine Kolcaba's theory of comfort (1995), were analyzed. A qualitative phenomenological study (Coelho, Parola, Escobar-Bravo, & Apóstolo, 2016) was conducted to understand the comfort and discomfort experiences of patients admitted to PCU.…”
Section: Phase II -Identifying/developing Appropriate Theorymentioning
confidence: 99%